DEVELOPING PRAGMATIC COMPETENCE IN EFL LEARNERS - Farmanov Gayrat Khujakulovich (Galaxy International Interdisciplinary Research Journal, 2023)
As EFL teachers, we need to be aware of the different ways in which pragmatic transfer manifests itself as it can have a profound impact on our students, their experiences within English speaking environments and on their interlanguage progress. Using English in a sociocultural appropriate way is vital for effective communication and for immersion into an English-speaking society and culture. This is why the role of EFL teacher and his understanding and awareness of L2 pragmatic competence and development are paramount.